Relationship Marketing Strategies in Building Long-Term Partnerships Between Contractor And Clients in the Property Sector - Ni Putu Pindia Maharani; Anak Agung Elik Astari; Ni Wayan Ari Sudiartini (Program Studi Akuntansi Universitas Islam Lamongan, 2025)
This study aims to analyze the influence of five dimensions of relationship marketing—communication, trust, commitment, empathy, and long-term orientation—on long-term partnerships between contractor companies and clients in the property sector, particularly in Tabanan, Bali. A quantitative method was applied using purposive sampling with 100 respondents. Data were analyzed using multiple linear regression with SPSS.